On the dynamics and stages of search under aggravated circumstances - Rimkutė, E. (Psichologija, 1968)
The article aims to demonstrate the dynamics and stages of aggravated search (and finding). For this purpose some stages of complex search activities have been distinguished.Figure exclusion (formation) is regarded as the first stage. Comparison of the excluded figure against the given gauge is the second stage. Different displays of this operation (unconscious and conscious comparison), their place and functions in the search process have been discussed. The third stage is making the final decision regarding the compared figure.
Keywords: aggravated search; figure; figure perception